Variation in loanword adaptation: A case from Mandarin Chinese. (July 2022) - Chen, Yangyu; Lu, Yu-An
Mandarin speakers tend to adapt intervocalic nasals as either an onset of the following syllable (e.g. Bruno → bù.lŭ .n uò ), as a nasal geminate (e.g. Daniel → dā n.n í.ěr ), or as one of the above forms (e.g. Tiffany → dì.fú. n í or dì.fē n.n í ). Huang and Lin (2013, 2016) identified two factors that may induce the nasal gemination repair: (1) when stress falls on the pre-nasal vowel and (2) when the pre-nasal vowel is a non-high lax vowel. They hypothesized that Mandarin Chinese speakers insert a nasal coda to perceptually approximate the stronger nasalization and longer syllable duration associated with the stressed syllables, and the shorter vowel duration of a lax vowel because the vowels in closed syllables are shorter in Mandarin. The results from two forced-choice identification experiments and an open-ended transcription task showed that although Mandarin speakers' choices of different repairs were indeed biased by the different phonetic manipulations, suggesting an effect of perceptual similarity, their decisions were mainly guided by native phonotactics. The overall findings suggest that phonotactic, phonetic, as well as non-linguistic (i.e. frequency) factors interact with each other, resulting in the variable adaptation pattern.